Analysis Students Addition Error in Writing Thesis Abstract Of English Education Department STKIP AL Maksum Langkat - Sari Adelina, Yunita; Neneng Sri Lestari; Suprayetno, Edi (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The focus of this research was to describe the addition errors detected in the writing of the thesis abstract, to figure out why they happened, and to figure out how they happened at the Department of English Education for Students at STKIP Al Maksum Langkat. This research revolves around the abstract of an undergraduate thesis from the English department. In this study, the descriptive qualitative method was applied. This study's data comes from ten abstract manuscripts of undergraduate thesis dissertations published in 2022. The steps in error analysis are collection, identification, description, explanation, and error evaluation. As illustrated by these statistics, the errors made by undergraduate students are additional words that can occur as a result of interlanguage interference, intralingual interference, insufficient command of English syntax and vocabulary.